Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2166/aqua.2011.013
|View full text |Cite
|
Sign up to set email alerts
|

Application of unidirectional flushing in water distribution pipes

Abstract: In this study unidirectional flushing (UDF) was conducted to improve the effectiveness of deposit removal from internal pipe walls and to provide information on pipe networks to enable operators to implement flushing in field. Four ductile cast iron pipes with epoxy-lined and cement-lined were selected for the practice of UDF. Water pressure was measured using a data logger equipped with a pressure gauge. The normal flow velocities of the networks were found to be 0.12 m/sec or below in the study area. Flushin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Even in this case, it was appropriate to end the cleaning by conventional flushing, to re-settle the incrustations in the pipe and flush out any accumulated air. According to [ 43 ], the daily flow rate in the water supply system was found to be ≤ 0.12 m·s −1 , therefore, it is advisable to flush at this flow velocity or lower. The flow velocity used in the given experiments corresponded to v = 0.066 m·s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Even in this case, it was appropriate to end the cleaning by conventional flushing, to re-settle the incrustations in the pipe and flush out any accumulated air. According to [ 43 ], the daily flow rate in the water supply system was found to be ≤ 0.12 m·s −1 , therefore, it is advisable to flush at this flow velocity or lower. The flow velocity used in the given experiments corresponded to v = 0.066 m·s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, changes in flow direction have a higher likelihood of causing water quality incidents compared to velocity criteria, as reported in the literature [24,25,27,36]. For instance, studies by Ahn et al [36] and Armand et al [37] indicated that backward flows are more efficient in suspending deposits or cleaning pipes compared to simple velocity changes. Similarly, when there is a change in flow direction within the pipe, it directly affects the detachment of previously stabilized scale [24,33].…”
Section: Potential Water Quality Risksmentioning
confidence: 95%